Pengaruh Lokasi dan Kualitas Produk terhadap Minat Beli Ulang Konsumen - Sari, Dwi Farida Ratna; Nurmaning, Bina Andri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
There are many different types of coffee shop businesses in Tulungagung that exist today, one of the many coffee shop businesses is the Coffee Shop. The more here in the Tulungagung area, the more people open coffee shop businesses. Researchers observe from time to time this type of coffee shop business is increasingly widespread in various corners of Tulungagung Regency both in its development and in terms of its business activists, researchers see opportunities in this coffee shop business can be called promising because the food / drinks provided are foods that are in great demand by consumers, the purpose of this study was to determine the effect of Location and Product Quality on Consumer Repurchase Interests at Luwin Ngujang Bridge 2 Tulungagung Shop, Data collection methods with questionnaires to obtain data on Location X1, Product Quality X2 and Consumer Repurchase Interest Y. The instrument used was in the form of questions with answers that were already available, based on research and discussion, the results of multiple linear regression equations were obtained so that it can be significant that Location has a positive influence on consumer repurchase interest at Luwin Ngujang Bridge 2 Tulungagung Shop. The t-test results for the Location variable are known to be tcount > ttable, which is 5.381 > 1.98472, with a significant value of 0.000 < 0.05. So, it is known that there is an influence of Location on consumer repurchase interest. Thus, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.